Advanced Artificial Intelligence Models and Its Applications - Zhou, Tao (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The field of Artificial Intelligence (AI) has undergone enormous expansion since its inception in the mid-20th century, as demonstrated by its application across an array of engineering and scientific challenges. Particularly in the last decade, AI has witnessed a significant breakthrough with the advent of deep learning, which has facilitated the employment of various AI models across a multitude of domains. This reprint features ten papers accepted for publication in the Special Issue titled "Advanced Artificial Intelligence Models and Their Applications," published in the MDPI Mathematics journal. These papers explore numerous facets of advanced artificial intelligence models and their applications, covering areas such as cybersecurity, image classification, logistics optimization, automatic music generation, human capital investment, writer recognition, remote sensing image indexing, target tracking, and more. These diverse subjects highlight the extensive scope and capability of AI models in tackling intricate challenges across distinct fields, underlining the vast potential inherent in this cutting-edge technology.